Network-Based Approaches in Bioinformatics and Cheminformatics: Leveraging IT for Insights - Pydipalli, Rajani (ABC Journal of Advanced Research, 2018)
Network-based approaches in bioinformatics and cheminformatics use computational methods and IT to investigate complicated biological and chemical systems. This review examines network-based analyses’ fundamentals, sophisticated techniques, and different applications in these disciplines. The study will investigate novel methods for integrating heterogeneous data sources to build comprehensive biological and chemical networks, apply advanced network analysis techniques to reveal hidden relationships and functional modules within these networks, and assess the efficacy of network-based approaches in elucidating complex biological processes and accelerating drug discovery Network-based approach literature. Secondary data sources are reviewed, focusing on secondary data-based review papers. Significant findings show how network-based methods affect biological processes, disease mechanisms, and medication development. For network-based bioinformatics and cheminformatics to succeed, policymakers must invest in data infrastructure, standardized data formats, and interdisciplinary collaboration. Network-based techniques can use IT to understand biological and chemical systems, shaping biomedical research and precision medicine.